2016
DOI: 10.1161/circulationaha.116.021618
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Post–Cardiac Arrest Myocardial Dysfunction Is Supported by Ca 2+ /Calmodulin-Dependent Protein Kinase II–Mediated Calcium Long-Term Potentiation and Mitigated by Alda-1, an Agonist of Aldehyde Dehydrogenase Type 2

Abstract: Background Survival after sudden cardiac arrest is limited by post-arrest myocardial dysfunction but understanding of this phenomenon is constrained by lack of data from a physiological model of disease. In this study, we established an in vivo model of cardiac arrest and resuscitation, characterized the biology of the associated myocardial dysfunction, and tested novel therapeutic strategies. Methods We developed rodent models of in vivo post-arrest myocardial dysfunction using extra-corporeal membrane oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
0
13
0
5
Order By: Relevance
“…Using an in vitro model of atherosclerosis, Alda-1 was effective in reducing 4-HNE-protein adducts, ER stress and apoptosis in smooth muscle cells [169]. In addition, activation of ALDH2 by Alda-1 reduced ROS and reactive aldehydes levels, mitigated calcium overload and dramatically improved resuscitation survival in an in vivo model of post-myocardial arrest dysfunction [170]. These studies established a critical connection between ALDH2 activity, cardiac function and heart failure.…”
Section: Therapies Targeting Mitochondria In Heart Failurementioning
confidence: 99%
“…Using an in vitro model of atherosclerosis, Alda-1 was effective in reducing 4-HNE-protein adducts, ER stress and apoptosis in smooth muscle cells [169]. In addition, activation of ALDH2 by Alda-1 reduced ROS and reactive aldehydes levels, mitigated calcium overload and dramatically improved resuscitation survival in an in vivo model of post-myocardial arrest dysfunction [170]. These studies established a critical connection between ALDH2 activity, cardiac function and heart failure.…”
Section: Therapies Targeting Mitochondria In Heart Failurementioning
confidence: 99%
“…(37) The hypothesis that VF increased cardiac injury explaining these adverse effects is intriguing though speculative. Myocardial dysfunction after CA has been attributed to calcium overload,(38) which parallels classic findings in myocardial infarction. (39) This mechanism may explain why Vaagenes found that lidoflazine therapy, a calcium antagonist, improved outcomes after VF-CA but not A-CA and free radical scavengers improved outcomes after A-CA not VF-CA.…”
Section: Discussionmentioning
confidence: 63%
“…However, some mRNAs that acted as the linear alternative transcript of those circRNAs were found to participate in various cellular processes associated with I/R injury. For instance, Calm3 is the linear transcript of circRNA_41204 (one of the top 5 decreased circRNAs in intestinal I/R) and it encodes calmodulin (CaM), a ubiquitous Ca 2+ -binding protein that regulates a vast array of Ca 2+ -sensitive biological events, which play important roles in the pathogenesis of I/R injury [28,29]. Wdfy1 is the linear transcript of circRNA_18944 (one of the top 5 decreased circRNAs in iPoC), and its protein product was found to recruit the signaling adaptor protein TRIF to Toll-like receptors (TLRs) 3 and 4, thereby mediating the activation of NF-κB and induction of inflammatory cytokines [30].…”
Section: Discussionmentioning
confidence: 99%